The Resolution of Religious Controversy in Multicultural Society in Indonesia - Fathurrahman Muhtar (AL-TAHRIR, 2018)
Abstract: The study has attempted to explain several issues, namely, the causes of religious and ethnic conflicts that occurred in Indonesia, the history of the success of Islam in decreasing conflict by developing tasamuh and various social-religious approaches that can be used as an effort to resolve religious conflicts. This research was library research by interpreting several references for collecting information related to the background of the conflict in Indonesia. The findings showed that There are several pint which worth noting. Firstly, that religious conflict in Indonesia is triggered by social, economic and political problems. Secondly, the presence of religious texts that tends to produce radical meaning, such as the interpretation of jihad and infidels. Thirdly, the existence of religious teaching integration into the culture. This study offers three forms of conflict resolution: The first resolution is that create religion as a form of reconciliation as it was the practice of tasamuh at the time of the Prophet Muhammad. Secondly: develop the theology of religious pluralism. The last is that understand religious reality with a multi-method approach including the history of religion, anthropology, sociology, philosophy and psychology.الملخص: تشرح هذه الدراسة عدة مواضيع هامة بما في ذلك الأسباب المختلفة للصراعات الدينية والعرقية التي حدثت في إندونيسيا. ثانيا: شرح تاريخ نجاح الإسلام في الحد من الصراع بتطوير التسامح الإسلامي. ﺛﺎﻟﺜﺎً: ﻣﺨﺘﻠﻒ اﻟﻨﻬﺞ اﻻﺟﺘﻤﺎﻋﻴﺔ - اﻟﺪﻳﻨﻴﺔ اﻟﺘﻲ ﻳﻤﻜﻦ اﺳﺘﺨﺪاﻣﻬﺎ ﻟﺤﻞ اﻟﻨﺰاﻋﺎت اﻟﺪﻳﻨﻴﺔ. تستخدم هذه الدراسة طريقتان وهما دراسة مكتبية وتاريخية فالأولى تستخدم في بيان شكل عدة الصراعات التي وقعت في إندونيسيا. ودراسة تاريخية تستخدم  لتحليل  معلومات حول خلفية النزاع في إندونيسيا. بعض النتائج التي توصلت إليها هذه الدراسة هي: أولا ، أن الصراع الديني في إندونيسيا ناجم عن مشاكل اجتماعية واقتصادية وسياسية. ثانياً: معنى النصوص الدينية التي تميل إلى أن تكون جذرية ، مثل معنى الجهاد ، ومعنى الكفار وما إلى ذلك. ثالثًا: إضفاء الطابع الرسمي على التعاليم الدينية في الثقافة. ومن أجل التغلب على أنواع الصراعات المختلفة ، يقدم هذا البحث ثلاثة أشكال لحل النزاعات ، وهي أولاً: جعل الدين شكلاً من أشكال السلام ، كما كان ممارسة تساموه في زمن النبي محمد. ثانيًا: تطوير علم اللاهوت للتعددية الدينية. ثالثًا: فهم الواقع الديني بمقاربة متعددة الاتجاهات بما في ذلك تاريخ الدين والأنثروبولوجيا وعلم الاجتماع والفلسفة وعلم النفس.Abstrak: Kajian ini menjelaskan beberapa topik penting di antaranya, yaitu pertama berbagai macam penyebab konflik agama dan etnik yang pernah terjadi di Indonesia.  Kedua, menjelaskan  sejarah keberhasilan Islam dalam meredam konflik dengan mengembangkan tasamuh Islam. Ketiga, berbagai   pendekatan-pendekatan sosial keagamaan yang dapat dijadikan sebagai upaya dalam menyelesaikan konflik agama. Penelitian ini menggunakan pendekatan kepustakaan berupa beberapa referensi tentang konflik yang pernah terjadi di Indonesia. Referensi tersebut digunakan untuk menggali informasi tentang latarbelakang terjadinya konflik di Indonesia. Beberapa temuan penelitian ini adalah: pertama, konflik agama di Indonesia disebabkan oleh masalah sosial, ekonomi dan politik.  Kedua: Pemaknaan atas teks-teks  agama yang cenderung radikal, seperti makna jihad, makna kafir dan sebagainya. Ketiga:  formalisasi ajaran agama kedalam budaya.  Maka untuk mengatasi berbagai macam konflik tersebut, penelitian ini menawarkan tiga bentuk penyelesaian konflik, yaitu pertama: menjadikan agama sebagai bina damai, sebagaimana praktek tasamuh pada masa Nabi Muhammad Saw. Kedua: Mengembangkan teologi pluralism agama. Ketiga: Memahami realitas keagamaan dengan pendekatan multimetodik diantaranya sejarah agama, antropologi, sosiologi, filsafat, psikologi.